Developing a wireless real-time automated home approach utilizing NI MyRIO microcontroller board and LabVIEW platform - Ahmad A. Alahmadi (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, a design process and a hardware implementation for a wireless real-time home automation system approach based on NI MyRIO microcontroller board and LabVIEW platform has been developed. The proposed automated system has two hardware elements: the first one is a personal computer as a system main server hosting the designed LabVIEW platform and the second element is a NI MyRIO microcontroller board for managing the operating between the appliances and the sensors. The appliances can be automatically monitored, controlled, and accessed in response to the signals from the related sensors or manually by the system end-user through smart phone based on Wi-Fi and cloud computing technology. To approve the reliability of the proposed automated system, a hardware realization for three appliances: temperature management, light energy saving, and biometric security system of face recognition with fingerprint check has been introduced. The proposed system has a simple structure, economically cost effective and flexible scaling up for a proper automated home future.